Synaptic vesicles have two distinct recycling pathways. - J. H. Koenig; Kazuo Ikeda (1996)
In this paper, evidence is presented that two distinct synaptic vesicle recycling pathways exist within a single terminal. One pathway emanates from the active zone, has a fast time course, involves no intermediate structures, and is blocked by exposure to high Mg2+/low Ca2+ saline, while the second pathway emanates at sites away from the active zone, has a slower time course, involves an endosomal intermediate, and is not sensitive to high Mg2+/low Ca2+. To visualize these two recycling pathways, the temperature-sensitive Drosophila mutant, shibire, in which vesicle recycling is normal at 19 degrees C but is blocked at 29 degrees C, was used. With exposure to 29 degrees C, complete vesicle depletion occurs as exocytosis proceeds while endocytosis is blocked. When the temperature is lowered to 26 degrees C, vesicle recycling membrane begins to accumulate as invaginations of the plasmalemma, but pinch-off is blocked. Under these experimental conditions, it was possible to distinguish the two separate pathways by electron microscopic analysis. These two pathways were further characterized by observing the normal recycling process at the permissive temperature, 19 degrees C. It is suggested that the function of these two recycling pathways might be to produce two distinct vesicle populations: the active zone and nonactive zone populations. The possibility that these two populations have different release characteristics and functions is discussed.